Bias, insecurity and the level of trust in the judiciary: the case of Brazil. Issue 1 (31st January 2018) - YEUNG, LUCIANA L.
Abstract: Are judges biased in their decisions? If so, what are the consequences? We propose a conceptual model that estimates the effects of judicial bias and insecurity on the trustworthiness of courts. Additionally, we empirically assess evidence of bias among justices at the Superior Court (STJ). For this purpose, we analyzed 1, 412 decisions from 1998 to 2008. Results do not show consistent strong bias toward either the debtor or the creditor. We test a second hypothesis: that Brazilian courts are unpredictable, creating high levels of judicial insecurity. Empirical results corroborate this idea. Finally, we relate the empirical results found in this paper with the conceptual model initially developed, and provide evidence measured by a nationwide survey on the trustworthiness of the judiciary. As our model predicted, preliminary results indicate that citizens have lower levels of trust in the judicial system if courts and judges are biased and unpredictable.